PENGARUH KOMPETENSI, PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA (Studi Pada Karyawan PT Golden Blossom Sumatera Kabupaten Penukal Abab Lematang Ilir) - Herani, Irenti Deskalia; Agusria, Lesi (Universitas Muhammadiyah Palembang, 2021)
The formulation of the problem in this study is is there the influence of competence, training and work discipline on employee performance at PT Golden Blossom Sumatera, Penukal Abab Lematang Ilir Regency. This type of research used in this study is associative. The population in this study were all employees of PT Golden Blossom Sumatera, Penukal Abab Lematang Ilir Regency, amounting to 113 people and the samples taken in this study were 83 respondents with the Simple Cluster Area sampling technique. The analysis method used is qualitative which is then quantified. The data analysis technique used in this study is multiple linear regression analysis, F test, t test and the coefficient of determination. The test results using multiple regression analysis show that Y = 0.064 + 0.402 X1 + 0.333 X2 + 0.401 X3. The simultaneous hypothesis test results show a significant influence between competence, training and work discipline on employee performance with the value of Fcount 6179.05 > Ftable 2.15, with a sig.F level of 0.000 < 0.10. Partially competence has a significant effect on employee performance with a value of tcount 1,815 > ttable 1,664, this is reinforced by the sig.F level of 0,000 <0.10 (significant). Partially training has a significant effect on employee performance with a value of tcount 2.704 > ttable 1.664, this is reinforced by the sig.t level of 0.000 < 0.10 (significant). Partially work discipline has a significant effect on employee performance with a value of tcount 3.562> ttable 1.664, this is reinforced by the sig.t level of 0.000 < 0.10 (significant). Reinforced with Adjusted R Square (coefficient of determination) of 0.996, this figure illustrates that employee performance can be influenced by competence, work discipline and organizational commitment by 99.6%, while the remaining 0.4% is influenced by variables not examined.